2009
DOI: 10.1016/j.archger.2008.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of aging and falling: The Beaver Dam eye study

Abstract: Falls are an important cause of morbidity in older adults and are an important source of health care spending. We hypothesize that falls are associated with systemic biomarkers of aging. The following functions, measured at the 1998-2000 and 2003-05 examinations of the Beaver Dam Eye study, were considered to be biomarkers of aging (frailties): poorer visual acuity, contrast sensitivity or discrepant vision between the eyes, inability to rise from a chair, slower gait time, poorer hand grip strength, and lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 38 publications
1
42
1
1
Order By: Relevance
“…[15][16][17][18][19] However, recent research has found that reduced contrast sensitivity and depth perception are more important visual risk factors for falls. 14,16,[20][21][22] It should be noted that the majority of existing studies were conducted in developed countries, using the general older population. No study has examined visual risk factors for falls among cataract patients specifically and no study has been conducted in Vietnam, where older adults have much poorer vision than in developed countries.…”
Section: Introductionmentioning
confidence: 97%
“…[15][16][17][18][19] However, recent research has found that reduced contrast sensitivity and depth perception are more important visual risk factors for falls. 14,16,[20][21][22] It should be noted that the majority of existing studies were conducted in developed countries, using the general older population. No study has examined visual risk factors for falls among cataract patients specifically and no study has been conducted in Vietnam, where older adults have much poorer vision than in developed countries.…”
Section: Introductionmentioning
confidence: 97%
“…242 On the other hand, vision loss can contribute to depression, 243 isolation, 243 disruptive behaviors 244 and falls. 245 Therefore, eye care professionals can confidently offer evidence-based therapies to older individuals having an ocular condition necessitating treatment, knowing that not only will their vision improve, but so will many other aspects of their life.…”
Section: Reflecting On the Benefits Of Improving Vision In Dementiamentioning
confidence: 99%
“…All of these difficulties contribute to an extensive economic burden to the society. [4][5][6] Therefore, early identification and modification of the risk factors for cataracts are meaningful from a public health perspective. A growing body of research has been conducted to investigate risk factors associated with the development and progression of age-related cataracts.…”
Section: Introductionmentioning
confidence: 99%